Analisis Penilaian Tingkat Kesehatan Bank Umum BUMN Menggunakan Metode RGEC - Wenny Ana Adnanti; Iin Indarti; Elma Muncar Aditya (ECONBANK: Journal of Economics and Banking, 2022)
This study aims to determine the performance of state-owned commercial banks in terms of bank soundness assessment, namely: Risk-profile, Good Corporate Governance (GCG), Earning and Capital (RGEC). The research method used is descriptive research with a qualitative approach. The data in this study uses secondary data obtained from the financial statements of state-owned commercial banks for the period 2018 - 2020. The data analysis technique uses a risk approach (Risk - Based Banking Rate) with an assessment coverage of RGEC factors. The results of this study indicate the performance of state-owned commercial banks in terms of: (1) The risk-profile is in a healthy condition with an average NPL ratio of 1.18%, 1.64%, and 1.27%, and the ratio LDR are 96.28%, 99.05%, and 84.41%, respectively. (2) GCG period 2018 – 2019 with a composite value of 1.75 healthy criteria, and the 2020 period with a composite value of 1.5 very healthy criteria (3) Earning with an average ROA ratio of 3.21% criteria very healthy, 3.54% very healthy criteria, and 1.62% healthy criteria, NIM ratio of 5.16% very healthy criteria, 4.96% healthy criteria and 4.48% healthy criteria, BOPO ratio of 73.75 % very healthy criteria, 80.02% very healthy criteria and 81.96% very healthy criteria. (4) Capital is in a very healthy condition with average CAR ratios of 29.2%, 30.62% and 27.34%. (5) RGEC as a whole is in a very healthy rating.